Strategi Pengembangan Kewirausahaan di Daerah Pedesaan (Studi Kasus Kewirausahaan Jamur Tiram di Desa Bulaklo, Kec. Balen, Kabupaten Bojonegoro): Pengabdian - Heny Suhindarno; Musta’ Ana; Lita Tri Cahyaningrum; Nadela Putri Rumaysa (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This community service project is entitled "Entrepreneurship Development Strategy in Rural Areas (Case Study of Oyster Mushroom Entrepreneurship in Bulaklo Village, Balen District, Bojonegoro Regency)." The activity aims to increase community capacity in oyster mushroom cultivation and strengthen business institutions. The method used is participatory mentoring through technical training, business management counseling, and group formation. As a result, community skills improved, two business groups were formed, productivity increased by approximately thirty percent, and farmers' incomes increased by twenty to twenty-five percent. Mushroom products also began to be marketed more widely, including through social media. This program demonstrates that entrepreneurship based on local potential can be an effective strategy for village economic empowerment and is worthy of replication in other areas.